RICE HUSK ASH-CATALYZED CO-PYROLYSIS OF EMPTY FRUIT BUNCH AND HIGH-DENSITY POLYETHYLENE FOR HYDROCARBON PRODUCTION (Jurnal Teknologi (Sciences & Engineering), 2025)
Agricultural residues like empty fruit bunch (EFB) are valuable as it can be converted to fuel via pyrolysis, with plastic waste resources like high-density polyethylene (HDPE). Meanwhile, rice husk ash (RHA) is useful for catalyst synthesis due to its high silica content. The objective of this study is to investigate the co-pyrolysis of EFB and HDPE over RHA-based catalyst via fixed-bed reactor for hydrocarbon-rich bio-oil. Experiments were conducted where pyrolysis temperature was first varied followed by the catalyst-to-feedstock ratio (CTF). Bio-oil with the highest hydrocarbon content (70.4%) was achieved at 550 °C and a CTF of 1:1. Comparison was made with a similar run using Hydrogen exchanged Zeolite Socony Mobil-5 (HZSM-5) catalyst, where using HZSM-5 catalyst produced bio-oil containing 74.4% hydrocarbon. It was concluded that RHA is a valuable resource for catalyst synthesis and can be applied to pyrolysis for improved bio-oil quality in terms of hydrocarbon content.